A study on plasma norepinephrine and epinephrine levels in TCM liver syndromes - Yan, D; Jin, Y; Zhang, X; Li, J; Shi, L; Chen, Z; Li, X; Lin, Y (Journal of traditional Chinese medicine, 1997)
The levels of plasma norepinephrine (NE) and epinephrine (E) were determined by HPLC in 220 patients with various TCM liver syndromes, and in 96 healthy subjects as controls. The plasma NE and E contents were higher in patients with liver excess syndromes, including Ganqi Yujie (GQYJ [symbol: see text]) syndrome, Ganyang Shangkang (GYSK [symbol: see text]) syndrome, Ganhuo Shangyan (GHSY [symbol: see text]) syndrome, and Ganyang Huafeng (GYHF [symbol: see text]) syndrome; while they were lower in patients with liver deficiency syndromes, including Ganqixu (GQX [symbol: see text]) syndrome, Ganxuexu (GXX [symbol: see text]) syndrome, and Ganyinxu (GYX [symbol: see text]) syndrome. Futhermore, when Ganshen Yinxu (GSYX [symbol: see text]) syndrome was turned into GYSK and then into GYHF, the plasma NE and E contents increased in order of precedence; while when GQYJ was turned into Ganyu Pixu (GYPX [symbol: see text]) syndrome, both NE and E contents decreased. The results suggest that the plasma NE and E contents are reliable objective parameters for the study of pathophysiological basis of the liver excess and liver deficiency syndromes, and the liver-kidney and liver-spleen interrelated syndromes.